Balantidiasic colitis. Report of a fatal case in human from Huancavelica, Peru - Vásquez Jiménez, Wenceslao (1999)
The case of a 60-year-old farmer and swinerherd, with Balantidiasic colitis is reported. He had felt well until 10 days, when he presents a dysentery that progressed to lower gastrointestinal bleeding. Diagnosis was made through anoscopy and rectal swabs. Stained and fresh stools were taken, showing a number of Balantidium coli trophozoites. Despite the treatment started (metronidazol 750 mg t.i.d.), his condition worsened. Anatomopathological examinations performed post mortem showed pancolonic damage with a quiet amount of ulcers and whole colonic wall microperforations, with trophozoites at the bottom of ulcers. One of his two pigs was also infected. This report adressed the importance of considering this entity within the differential diagnosis of dysentery among rural areas.